Community diagnosis in efforts to reduce new cases of pulmonary tuberculosis at the kresek health center - Wilda Najmi Hentihu; Ernawati (Science Midwifery, 2023)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis. It is estimated that nearly 2 billion people are infected with M. tuberculosis. Every year, around 10 million people get TB disease and 1.6 million people die from it. According to data from the Kresek District Public Health Center, there has been an increase in TB cases in the last 3 years. This activity aims to reduce the number of new cases of pulmonary TB in the working area of the Kresek Health Center. problem identification using paradigm Blum, priority problem with Delphi non-scoring technique, identify root cause problems with Fishbone, and an intervention plan was developed. Evaluation of activities is carried out with a systems approach. The results of problem identification found that lifestyle factors play a role in the high number of new cases of pulmonary TB. The results of the identification of the root causes revealed that there was a lack of public knowledge about pulmonary TB due to a lack of education, so counseling was chosen as one of the educational media. Counseling was carried out to the community and the results of the intervention found that there was an increase in knowledge in the Kresek village community. The conclusion is that the community diagnosis obtained in the working area of the Kresek Health Center is pulmonary TB. Kresek Village is a location that has the main problem of pulmonary TB. After the intervention, there was an increase in the knowledge of the people who attended the counseling, so community diagnosis activities were suggested to address other health problems